2013
DOI: 10.1007/s00404-013-2747-6
|View full text |Cite
|
Sign up to set email alerts
|

Early amniotomy after vaginal misoprostol for induction of labor: a randomized clinical trial

Abstract: Early amniotomy after vaginal misoprostol for labor induction is associated with higher successful vaginal delivery rate, shorter labor duration and better neonatal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…3,6 Despite the differences in definition used, almost all studies show a reduction in the duration of labor with early amniotomy. 3,5,6,8,10 The association of early amniotomy with route of delivery, however, has been inconsistent. Some studies have demonstrated an increased risk of cesarean 3,4,11,12,14 while others have reported no significant difference, 6,[8][9][10]17 and one noted a decreased risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,6 Despite the differences in definition used, almost all studies show a reduction in the duration of labor with early amniotomy. 3,5,6,8,10 The association of early amniotomy with route of delivery, however, has been inconsistent. Some studies have demonstrated an increased risk of cesarean 3,4,11,12,14 while others have reported no significant difference, 6,[8][9][10]17 and one noted a decreased risk.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated an increased risk of cesarean 3,4,11,12,14 while others have reported no significant difference, 6,[8][9][10]17 and one noted a decreased risk. 5 Variation in study design and adoption of a more modern labor curve likely contribute to these discrepant outcomes. Overall, previous retrospective cohort studies were more likely to demonstrate an increase in cesarean compared with randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early artificial rupture of membranes (AROM) has been shown to decrease the duration of labour induction when defined as AROM <3 or 4 cm dilation, [5][6][7] AROM <1 h after transcervical Foley removal, 8 and AROM concurrent with or prior to oxytocin initiation. 6,9 The findings regarding an association between early AROM and caesarean delivery in these studies are conflicting, and evidence about the utility of early AROM in multiparous induction is lacking. Furthermore, no prior observational cohort study or randomised controlled trial has been sufficiently powered to evaluate the association between early AROM and rare adverse outcomes such as severe maternal and neonatal morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Many providers have concerns about the potential increase in complications such as umbilical cord prolapse, caesarean delivery, infection, and neonatal intensive care unit admission. Early artificial rupture of membranes (AROM) has been shown to decrease the duration of labour induction when defined as AROM <3 or 4 cm dilation, AROM <1 h after transcervical Foley removal, and AROM concurrent with or prior to oxytocin initiation . The findings regarding an association between early AROM and caesarean delivery in these studies are conflicting, and evidence about the utility of early AROM in multiparous induction is lacking.…”
Section: Introductionmentioning
confidence: 99%